Audiovisual virtual reality for emotion induction: a dataset of physiological responses - Luz Maria Alonso-Valerdi; Sharon Ramirez-Lechuga; David I. Ibarra-Zarate (Scientific Data)
Abstract This dataset provides demographic (age and sex), psychometric, and physiological data from 28 participants (20 males, 8 females) aged 19–27 years. Psychometric assessments include four questionnaires: the Emotion Regulation Questionnaire, Self-Assessment Manikin, and two perception-related scales (EmFacs and Uncanny Valley). Physiological signals recorded include electroencephalography, blood volume pulse, galvanic skin response, and skin temperature. Emotion induction was conducted using two virtual environments designed to elicit distinct emotional states: happiness (an outdoor natural forest) and anger (a subway car), with emotional stimuli delivered through speech by a digital human. Physiological responses were recorded at baseline and during immersion in the virtual environments. This dataset can support research on affective computing, human-computer interaction, and emotion recognition.